Students’ Interest in Learning, Self-Motivation and Adult Students’ Academic Commitment in Universities in Cross River State, Nigeria - Omori, A. E.; Onwuchekwa, N. J. (Journal of Research in Adult and Continuing Education, 2025)
This study investigated how students’ interest in learning and self-motivation influence adult students’ academic commitment in universities in Cross River state. A descriptive survey design was adopted and the population of the study consisted of adult students aged 22 to 45 years in the multi-stage sampling techniques were employed to select 362 undergraduate students from two universities in the state. Data was obtained through a well validated questionnaire titled: Students’ Interest, Self-Motivation and Academic Commitment Questionnaire (SISMACQ). The reliability index of the instrument obtained through KR-20 reliability method was .77. Two research questions guided the study and One-way Analysis of Variance was applied to analyze data collected from the respondents at .05 significance level. The results obtained from the data analyses revealed that students’ interest in learning and self-motivation significantly influence adult student’ academic commitment in the universities. It is therefore concluded that students’ interest in learning and self-motivation are important variables influencing adult students’ academic commitment. Thus, it was recommended among others that adult students should be encourage to develop high interest in learning and self-motivation in order to foster high and quality academic commitment in the universities.